Assessment of the Effectiveness of Technology Transfer Entities - Olga PYATAEVA; Alexander ANISIMOV; Artyom GAVRILYUK; Elena BORISOVA; Oleg SKRYABIN (Communications of International Proceedings, 2020)
In the context of the analysis of the various methodical approaches to the assessment of the subjects of technology transfer, it can be stated that there is no uniform methodology for assessing such effectiveness. The global scientific community recognizes that it is necessary to establish common methodological standards for the analysis of technology transfer processes in order to understand current trends and development potentials in the areas of technology transfer, but this has not yet been achieved. For Russia, this means that, in the absence of a single standard, the Russian innovation community can develop its national standards for evaluating the effectiveness of the technology transfer process, taking into account the national specificities of the process of commercializing innovation. The authors of this paper hold the view that the efficiency of the innovation process is determined by the efficiency of the technology transfer as its main instrument.
Keywords: Innovation; technology transfer; efficiency; technologies; Russian economy; economic efficiency; technology transfer entities; TT.